2019
DOI: 10.1002/pros.23880
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shock wave therapy decreases COX‐2 by inhibiting TLR4‐NFκB pathway in a prostatitis rat model

Abstract: Background This study aims to evaluate the effect of extracorporeal shock wave therapy (ESWT) on chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) and to explore the mechanism. Methods RWPE‐2 cells were randomly divided into three groups: (a) RWPE‐2 group (normal control), (b) LPS groups (lipopolysaccharide inducing inflammation) and (c) ESWT groups (LPS induced RWPE‐2 treated by ESWT). After ESWT was administered, cells and supernatant were collected for enzyme‐linked immunosorbent assay (ELISA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 24 publications
0
34
0
1
Order By: Relevance
“…In addition, mPGES-1/PGE 2 mediates the development and progression of prostate cancer 12 , 13 . As a responsive inflammatory factor, NFκB interacts with the COX-2/PGE pathway to mediate the progressions of prostatitis 14 and prostate cancer 15 . Lipocalin-type prostaglandin D synthase (L-PGDS) is a bifunctional protein that catalyzes the synthesis of prostaglandin D 2 and functions as a transporter of lipophilic substances.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mPGES-1/PGE 2 mediates the development and progression of prostate cancer 12 , 13 . As a responsive inflammatory factor, NFκB interacts with the COX-2/PGE pathway to mediate the progressions of prostatitis 14 and prostate cancer 15 . Lipocalin-type prostaglandin D synthase (L-PGDS) is a bifunctional protein that catalyzes the synthesis of prostaglandin D 2 and functions as a transporter of lipophilic substances.…”
Section: Introductionmentioning
confidence: 99%
“…As we know, the TLR4/NF-κΒ signaling pathway is activated in CP. 10 EAP mice had increased TLR4 expression and nuclear translocation of NF-κΒ, with an increase in the inflammation score, suggesting that the successfully construction of EAP model. In inflammation, TLR4 is one of the most critical cytokines, 11 while NF-κΒ as the downstream target of TLR4 is able to regulate the release of inflammatory factors (IL-6, IL-8, IL-1β, and TNF-α), thereby gaining an important role in the inflammation, oxidative stress, and immune response.…”
Section: Discussionmentioning
confidence: 95%
“…Toll-like receptors (TLRs) are critical to inflammation and immune and pathogen recognition, and among the TLRs, TLR4 has been confirmed to be associated with CP. 10,11 As a TLR member, TLR4 can mediate the activation of nuclear factor-kappa B (NF-κΒ) and cytokine synthesis by the MyD88 pathway, thereby participating in the pathogenesis. 12 Recently, miR-155 deficiency was reported to protect mice from alcohol-induced increase in inflammatory cytokines, and the activated NF-κB was revealed in WT but not in miR-155 knockout alcohol-fed mice.…”
Section: Introductionmentioning
confidence: 99%
“…Jeon et al recently showed LESW therapy decreases COX-2 by inhibiting TLR4-NFκB pathway in a prostatitis rat model. TRAF2 regulator in ERK1/2 inhibition significantly reduced inflammation [33]. The above-mentioned signaling events co-operatively induce inflammation with different level of the expression of IL-1β, IL-6, and other inflammatory molecular through different stimulation models.…”
Section: Discussionmentioning
confidence: 99%